Investment in Development of Higher Education Facilities from Central Budget - A Case Study of Vietnam - Ha, Pham Thanh (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In all periods, the State always plays an important and leading role in investing in educational development with different plans and levels. Investment in higher education is often considered in some fields, such as investment in facilities, investment in improving teaching quality, investment in scientific research activities, practice and access to jobs, for improving working skills... This article aims to focus on researching investment from the central budget for the development of higher education facilities in Vietnam. The research results contribute to suggesting to state managers a number of solutions in planning investment capital as well as effectively managing and organizing budget investment capital for not only higher education but also in many other investment fields.